Calligraphy Learning: Analysis of Guidance at Al-Quran Calligraphy Studio - Insani, Erikafatul; Anam, Nurul (JURNAL ISLAM NUSANTARA, 2023)
This research aims to provide a solution to the complex and challenging nature of learning calligraphy, preserve the art of calligraphy, and be able to provide achievements to students in the field of calligraphy art and play an essential role as a stimulator that stimulates the development of competent human resources in preserving Islamic cultural treasures in the form of calligraphy art. This research uses a qualitative approach with a case study type of research in Dar el-Khat Jember. Data collection was carried out through observation and interviews based on in-depth studies. The research results show that Dar el-Khat Jember has several unique lessons compared to other calligraphy art studios. This is revealed by the existence of three types of guidance, including (1) Guidance on the Introduction to the History of Al-Qur'an Calligraphy, (2) Guidance on Pure Calligraphy Learning, (3) Guidance on the development of applied calligraphy skills. Learning Al-Qur'an calligraphy at Dar el-Khat Jember makes it easier for students to learn Al-Qur'an calligraphy, increases mastery of various types of calligraphy, preserves the art of calligraphy, and stimulates the development of competent human resources in maintaining the art of calligraphy and Islamic culture.